Extreme Klimaereignisse und Hungerkatastrophen in den Prophetenbüchern - Kipfer, Sara (Vetus Testamentum / Supplements, 2023)
"Extreme climate events and famines are among the most continuous problems that humans have had to deal with throughout the ages. At the same time, they are closely intertwined with temporal, spatial and social conditions. Using methods of historical hunger research and the established concept of vulnerability, the texts of the Hebrew Bible are examined to determine how people perceived, interpreted and coped with extreme climate events. In doing so, it becomes apparent that the texts never provide simple, monocausal explanations, but rely on a number of different, sometimes contradictory statements. God, humans and nature appear in this conception as actors who interact with each other and share equal responsibility for the catastrophe"--